2014
DOI: 10.1186/1472-6882-14-185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of complementary and alternative medicine use among diabetic patients in Beirut, Lebanon: a cross-sectional study

Abstract: BackgroundPatients with Type 2 Diabetes Mellitus (T2DM) are increasingly using complementary and alternative medicine (CAM) therapies due to difficulty in adhering to the therapeutic regimens and lifestyle changes necessary for disease management. Little is known about the prevalence and mode of CAM use among patients with T2DM in Lebanon.ObjectiveTo assess the prevalence and modes of CAM use among patients with T2DM residing in Beirut, Lebanon.MethodsA cross-sectional survey of T2DM patients was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
66
6
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 51 publications
(66 reference statements)
15
66
6
6
Order By: Relevance
“…Çalışmamıza katılan hastaların TAT kullanım oranlarının %48.1 olduğu belirlenmiştir Ülkemizde yapılan çalışma-larda, diyabetli hastalarda TAT kullanma oranları %18.5-70.5 (5,12,20,21); farklı ülkelerde yapılan çalışmalarda ise diyabetli hastalarda TAT kullanım oranları %38.1-63 arasında değişmektedir (22)(23)(24). TAT kullanım oranları arasındaki bu farklılığın, yaşanılan toplumun TAT'a iliş-kin değerlerinin, inançlarının, kültürel özelliklerinin ve TAT kapsamında düşündükleri uygulamaların farklı olmasından kaynaklandığı belirtilmektedir (5,22,23).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Çalışmamıza katılan hastaların TAT kullanım oranlarının %48.1 olduğu belirlenmiştir Ülkemizde yapılan çalışma-larda, diyabetli hastalarda TAT kullanma oranları %18.5-70.5 (5,12,20,21); farklı ülkelerde yapılan çalışmalarda ise diyabetli hastalarda TAT kullanım oranları %38.1-63 arasında değişmektedir (22)(23)(24). TAT kullanım oranları arasındaki bu farklılığın, yaşanılan toplumun TAT'a iliş-kin değerlerinin, inançlarının, kültürel özelliklerinin ve TAT kapsamında düşündükleri uygulamaların farklı olmasından kaynaklandığı belirtilmektedir (5,22,23).…”
Section: Discussionunclassified
“…TAT kullanım oranları arasındaki bu farklılığın, yaşanılan toplumun TAT'a iliş-kin değerlerinin, inançlarının, kültürel özelliklerinin ve TAT kapsamında düşündükleri uygulamaların farklı olmasından kaynaklandığı belirtilmektedir (5,22,23). TAT kullanan hastaların büyük çoğunluğunun (%67,9) sadece bitkisel uygulamalar kullandıkları saptanmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In this context, several studies have examined the influence of sociodemographic and clinical characteristics of diabetes patients on traditional medicine use (4,8,14). Moreover, a review of traditional medicine use among diabetic populations has indicated that some sociodemographic and clinical factors are associated with greater use of traditional medicine (7).…”
Section: Introductionmentioning
confidence: 99%